2022
DOI: 10.1021/acs.nanolett.2c01005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Intracellular Transcytosis of Nanoparticles by Degrading Extracellular Matrix for Deep Tissue Radiotherapy of Pancreatic Adenocarcinoma

Abstract: Intracellular transcytosis can enhance the penetration of nanomedicines to deep avascular tumor tissues, but strategies that can improve transcytosis are limited. In this study, we discovered that pyknomorphic extracellular matrix (ECM) is a shield that impairs endocytosis of nanoparticles and their movement between adjacent cells and thus limits their active transcytosis in tumors. We further showed that degradation of pivotal constituent of ECM (i.e., collagen) effectively enhances intracellular transcytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…During transcytosis, biomacromolecules are internalized by cells and excreted from the body ( Niu et al, 2021 ). Transcytosis has been proven to be an effective approach to improve the penetration of nanoparticles into tumors ( Wang et al, 2022 ).…”
Section: Extravascular Targeting Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…During transcytosis, biomacromolecules are internalized by cells and excreted from the body ( Niu et al, 2021 ). Transcytosis has been proven to be an effective approach to improve the penetration of nanoparticles into tumors ( Wang et al, 2022 ).…”
Section: Extravascular Targeting Nanoparticlesmentioning
confidence: 99%
“…A tumor-specific ONOO − nanogenerator (PM@CDDP/SNP, abbreviated as PMCS) was designed to produce ONOO − and more matrix metalloproteinases in a specific TME, and degrade its dense ECM, enhancing the EPR effect and promoting drug penetration and accumulation deep in the tumor ( Chen Y. et al, 2021 ). Wang et al (2022) designed nanoparticles modified with collagenase and demonstrated that the endocytosis of nanoparticles could be effectively increased by degrading collagen, indicating that the dense fibrous collagen prevented the penetration of nanomolecules and chemotherapeutic drugs into tumors. Hyaluronic acid binds to the CD44 receptor, upregulated in various cancer cells, which improves ECM targeting and has good therapeutic potential in some cancers ( Liu et al, 2018 ; Choi et al, 2019 ; Wang X. et al, 2021 ).…”
Section: Extravascular Targeting Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 105 ] Similarly, a pH‐responsive collagenase‐loaded transcytosis gold NP facilitated NP penetration and sensitized pancreatic adenocarcinoma in mice to radiation therapy. [ 106 ] Such combination and co‐formulation approaches are particularly useful for highly stromal cancers with dismal treatment prospects, and they may also hold potential for the treatment of fibrotic disorders.…”
Section: Intravenous Deliverymentioning
confidence: 99%
“…[32] In addition, sophisticated nanomedicines have shown effective penetration into solid tumors by means of active transcytosis, which generated extraordinary antitumor efficacy. [32][33][34][35][36][37][38] However, the underlying mechanism to develop well-defined nanoparticles with active transcytosis capability has been unclear. Ferritin, a natural protein with an outer diameter of 12 nm and an inner diameter of 8 nm, has been widely studied by us and others as drug delivery carriers due to its cage-like structure and intrinsic affinity to the transferrin receptor 1 (TfR-1) on many tumor cells.…”
Section: Introductionmentioning
confidence: 99%